Preparation method of composite solid electrolyte membrane and composite solid electrolyte membrane

By mixing the electrolyte and halide electrolytes of the halide, and the polymer monomer and the cause, it is sprayed on the base and is treated with light and heating to form a composite solid electrolyte film. Achieve efficient and simple membrane preparations, improved battery performance.

CN119381535APending Publication Date: 2025-01-28CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411644911.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The double-layer composite electrolyte membrane prepared by traditional wet layer coating is prone to solvent residue problems, resulting in a decrease in ionic conductivity and affecting battery performance. The existing dry process flow is complex, which is not conducive to mass production.

Method used

By mixing the electrolyte and halide electrolytes of the sulfide and halide electrolytes, respectively, the polymer monomer and the cause, forming a sulfur -containing mixture and halogen -oriented mixture, and spraying these mixtures on the base. After removing the base, the final composite solid electrolyte film is obtained.

Benefits of technology

This method simplifies the process of process, improves the mechanical strength, density and ion transmission capacity of the composite solid electrolyte, suitable for mass production, and shows high energy density and improved cycle life in full solid batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381535A_ABST
    Figure CN119381535A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a composite solid electrolyte membrane and the composite solid electrolyte membrane, and the preparation method comprises the following steps: uniformly mixing a sulfide electrolyte and a halide electrolyte with a polymer monomer and an initiator respectively to obtain a sulfur-containing mixture and a halogen-containing mixture respectively; spraying a sulfur-containing mixture on the substrate, and spraying a halogen-containing mixture on the sulfur-containing mixture to obtain an electrolyte membrane precursor; carrying out light treatment on the electrolyte membrane precursor to obtain an electrolyte membrane prepolymer; carrying out heating treatment on the electrolyte membrane prepolymer to obtain an electrolyte membrane full polymer; and removing the substrate in the electrolyte membrane full polymer to obtain the composite solid electrolyte membrane. In the embodiment of the invention, the sulfide electrolyte and the halide electrolyte are combined together through in-situ polymerization of the polymer monomer under illumination, and the preparation method which is simple in process and can be used for batch production is provided. According to the preparation method, the mechanical strength, compactness and ion transmission capability of the composite solid electrolyte membrane can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a preparation method of a composite solid electrolyte membrane and a composite solid electrolyte membrane. Background Art

[0002] All-solid-state batteries use non-flammable solid electrolytes to replace the flammable organic liquid electrolytes in traditional batteries, which greatly improves the safety of the battery. While improving safety, all-solid-state batteries can better adapt to high-energy positive and negative electrode materials and reduce system weight, thereby achieving a simultaneous increase in energy density. All-solid-state batteries are the next generation technology closest to industrialization, which has become a consensus in the industry and the scientific community.

[0003] All-solid-state batteries can have both high energy and high power density while greatly improving safety, and have great application prospects in the fields of new energy vehicles and national defense. One of the research focuses of all-solid-state batteries is solid electrolyte membranes. Among them, sulfide solid electrolytes have the advantages of high ionic conductivity, good mechanical ductility, and good interface contact with electrodes, while halide solid electrolytes have the advantages of high stability to the positive electrode and easy preparation. Therefore, combining the two to prepare composite solid electrolyte membranes has become a key research direction for solid electrolyte membranes.

[0004] The preparation process of the double-layer composite electrolyte membrane prepared by traditional wet layered coating is prone to solvent residue problems, which leads to a decrease in the ionic conductivity of the electrolyte membrane, resulting in poor battery performance. In addition, solvent recovery also greatly increases production costs. In this regard, researchers usually use a solvent-free dry process to eliminate the effect of solvents on the performance of the electrolyte membrane. However, most of the existing dry processes are complicated and not conducive to mass production. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a method for preparing a composite solid electrolyte membrane and a composite solid electrolyte membrane.

[0006] In a first aspect, the present application discloses a method for preparing a composite solid electrolyte membrane, comprising:

[0007] The sulfide electrolyte and the halide electrolyte are respectively mixed with the polymer monomer and the initiator to obtain a sulfur-containing mixture and a halogen-containing mixture;

[0008] spraying a sulfur-containing mixture on a substrate, and spraying a halogen-containing mixture on the sulfur-containing mixture to obtain an electrolyte membrane precursor;

[0009] The electrolyte membrane precursor is subjected to light treatment to obtain an electrolyte membrane prepolymer;

[0010] The electrolyte membrane prepolymer is subjected to a heating treatment to obtain an electrolyte membrane full polymer;

[0011] The substrate in the electrolyte membrane polymer is removed to obtain a composite solid electrolyte membrane.

[0012] In some possible embodiments,

[0013] In the sulfur-containing mixture, the mass proportions of sulfide electrolyte, polymer monomer and initiator are 80%-99%, 1%-20% and 0.01%-1% respectively;

[0014] In the halogen-containing mixture, the mass proportions of halide electrolyte, polymer monomer and initiator are 80%-99%, 1%-20% and 0.01%-1% respectively.

[0015] In some possible embodiments,

[0016] The sulfide electrolyte includes one or more of a lithium germanium phosphorus sulfur electrolyte and a lithium phosphorus sulfur chlorine electrolyte;

[0017] The halide electrolyte includes one or more of a lithium yttrium bromine electrolyte, a lithium indium chloride electrolyte, a lithium indium bromine electrolyte, and a lithium zirconium chloride electrolyte;

[0018] The polymer monomers include one or more of butyl acrylate, polyethylene glycol diacrylate, methyl methacrylate, trifluoroethyl methacrylate and pentaerythritol triacrylate;

[0019] The initiator includes one or more of azobisisobutyronitrile, benzophenone, thioxanthone, camphorquinone and bisimidazole.

[0020] In some possible embodiments,

[0021] The median particle size of the sulfide electrolyte is 0.3-10 microns.

[0022] The median particle size of the halide electrolyte is 0.3-10 microns.

[0023] In some possible embodiments,

[0024] The mixing method is one of roller milling, ball milling, high-speed mixing or three-dimensional mixing.

[0025] In some possible embodiments,

[0026] The substrate includes one or more of a polyester film and a polytetrafluoroethylene film;

[0027] The spray thickness of the sulfur-containing mixture is 10-300 microns;

[0028] The spraying thickness of the halogen-containing mixture is 0.5-100 microns.

[0029] In some possible embodiments,

[0030] The wavelength of the light source for the light treatment is 330-400 nanometers;

[0031] The duration of light treatment is 1-300 seconds.

[0032] In some possible embodiments,

[0033] The temperature of the heating treatment is 30-150 degrees Celsius;

[0034] The heating treatment time is 0.5-48 hours.

[0035] In a second aspect, an embodiment of the present application discloses a composite solid electrolyte membrane, which is prepared by any of the above-mentioned methods for preparing a composite solid electrolyte membrane.

[0036] In a third aspect, an embodiment of the present application discloses an all-solid-state battery, comprising the above-mentioned composite solid electrolyte membrane.

[0037] The technical solution provided by the embodiment of the present application has the following technical effects:

[0038] The preparation method of the composite solid electrolyte membrane in the embodiment of the present application includes: uniformly mixing a sulfide electrolyte and a halide electrolyte with a polymer monomer and an initiator respectively to obtain a sulfur-containing mixture and a halogen-containing mixture respectively; spraying the sulfur-containing mixture on a substrate, and spraying the halogen-containing mixture on the sulfur-containing mixture to obtain an electrolyte membrane precursor; subjecting the electrolyte membrane precursor to light treatment to obtain an electrolyte membrane prepolymer; subjecting the electrolyte membrane prepolymer to heat treatment to obtain an electrolyte membrane full polymer; removing the substrate from the electrolyte membrane full polymer to obtain a composite solid electrolyte membrane. In the embodiment of the present application, the sulfide electrolyte and the halide electrolyte are combined together by in-situ polymerization of the polymer monomer under light, providing a preparation method with a simple process and mass production. This preparation method can improve the mechanical strength, density and ion transport capacity of the composite solid electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 It is a schematic diagram of a process for preparing a composite solid electrolyte membrane provided in an embodiment of the present application;

[0041] Figure 2 It is a structural schematic diagram of a device for performing spraying and light treatment provided in an embodiment of the present application. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0043] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or server that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0044] The present application provides a method for preparing a composite solid electrolyte membrane. Sulfide electrolyte and halide electrolyte are combined together by in-situ polymerization of polymer monomers under light, providing a preparation method with simple process and mass production. Moreover, the preparation method is conducive to improving the mechanical strength, compactness and ion transmission capacity of the composite solid electrolyte membrane.

[0045] Figure 1 is a schematic diagram of a process for preparing a composite solid electrolyte membrane provided in an embodiment of the present application, such as Figure 1 As shown, the preparation method comprises:

[0046] S101: uniformly mixing the sulfide electrolyte and the halide electrolyte with the polymer monomer and the initiator respectively to obtain a sulfur-containing mixture and a halogen-containing mixture respectively.

[0047] In the examples of the present application, the required amount of sulfide electrolyte, polymer monomer and initiator are weighed, and the sulfide electrolyte, polymer monomer and initiator are uniformly mixed to obtain a sulfur-containing mixture. The required amount of halide electrolyte, polymer monomer and initiator are weighed, and the halide electrolyte, polymer monomer and initiator are uniformly mixed to obtain a halogen-containing mixture.

[0048] In the embodiment of the present application, the initiator is used to initiate a polymerization reaction between polymer monomers under certain conditions. Through the polymerization reaction, multiple polymer monomers can be converted into polymer chains, and the polymer network formed by the cross-linking of multiple polymer chains plays a supporting role for the sulfide electrolyte and the halide electrolyte, which helps to obtain a composite solid electrolyte membrane with self-supporting ability.

[0049] In the embodiment of the present application, in order to make the polymer network formed by the polymer monomer play a supporting role for the sulfide electrolyte and the halide electrolyte, the mass proportion of the polymer monomer in the sulfur-containing mixture and the halogen-containing mixture should not be too low. At the same time, in order to prevent the polymer network formed by too many polymer monomers from hindering the contact between the solid electrolyte (referring to the sulfide electrolyte and the halide electrolyte) particles in the composite solid electrolyte membrane finally formed and reducing the ionic conductivity of the composite solid electrolyte membrane, the mass proportion of the polymer monomer in the sulfur-containing mixture and the halogen-containing mixture should not be too low. Therefore, it is necessary to reasonably control the mass ratio of each substance in the sulfur-containing mixture and the halogen-containing mixture.

[0050] In some possible embodiments, in the sulfur-containing mixture, the mass proportions of the sulfide electrolyte, the polymer monomer, and the initiator are 80%-99%, 1%-20%, and 0.01%-1%, respectively.

[0051] Optionally, the mass proportion of the sulfide electrolyte in the sulfur-containing mixture is 80%; optionally, the mass proportion of the sulfide electrolyte in the sulfur-containing mixture is 89.5%; optionally, the mass proportion of the sulfide electrolyte in the sulfur-containing mixture is 99%.

[0052] Optionally, the mass proportion of the polymer monomer in the sulfur-containing mixture is 1%; optionally, the mass proportion of the polymer monomer in the sulfur-containing mixture is 10.5%; optionally, the mass proportion of the polymer monomer in the sulfur-containing mixture is 20%.

[0053] Optionally, the mass proportion of the initiator in the sulfur-containing mixture is 0.01%; optionally, the mass proportion of the initiator in the sulfur-containing mixture is 0.5%; optionally, the mass proportion of the initiator in the sulfur-containing mixture is 1%.

[0054] In some possible embodiments, in the halogen-containing mixture, the mass proportions of the halide electrolyte, the polymer monomer and the initiator are 80%-99%, 1%-20% and 0.01%-1% respectively.

[0055] Optionally, the mass proportion of the halide electrolyte in the halogen-containing mixture is 80%; optionally, the mass proportion of the halide electrolyte in the halogen-containing mixture is 89.5%; optionally, the mass proportion of the halide electrolyte in the halogen-containing mixture is 99%.

[0056] Optionally, the mass proportion of the polymer monomer in the halogen-containing mixture is 1%; optionally, the mass proportion of the polymer monomer in the halogen-containing mixture is 10.5%; optionally, the mass proportion of the polymer monomer in the halogen-containing mixture is 20%.

[0057] Optionally, the mass proportion of the initiator in the halogen-containing mixture is 0.01%; optionally, the mass proportion of the initiator in the halogen-containing mixture is 0.5%; optionally, the mass proportion of the initiator in the halogen-containing mixture is 1%.

[0058] In the embodiment of the present application, the sulfide electrolyte is a solid electrolyte containing sulfur element. The sulfide electrolyte includes one or more of lithium germanium phosphorus sulfur electrolyte and lithium phosphorus sulfur chlorine electrolyte.

[0059] In some possible embodiments, the median particle size of the sulfide electrolyte is 0.3-10 microns.

[0060] Optionally, the median particle size of the sulfide electrolyte is 0.3 microns; optionally, the median particle size of the sulfide electrolyte is 5.2 microns; optionally, the median particle size of the sulfide electrolyte is 10 microns.

[0061] In the embodiment of the present application, the halide electrolyte is a solid electrolyte containing a halogen element. The halide electrolyte includes one or more of a lithium yttrium bromine electrolyte, a lithium indium chloride electrolyte, a lithium indium bromine electrolyte, and a lithium zirconium chloride electrolyte, and the halide electrolyte is preferably a lithium yttrium bromine electrolyte and a lithium indium chloride electrolyte.

[0062] In some possible embodiments, the median particle size of the halide electrolyte is 0.3-10 microns.

[0063] Optionally, the median particle size of the halide electrolyte is 0.3 microns; optionally, the median particle size of the halide electrolyte is 5.2 microns; optionally, the median particle size of the halide electrolyte is 10 microns.

[0064] In an embodiment of the present application, the polymer monomer includes one or more of butyl acrylate, polyethylene glycol diacrylate, methyl methacrylate, trifluoroethyl methacrylate and pentaerythritol triacrylate.

[0065] Optionally, the polymer monomers in the sulfur-containing mixture and the halogen-containing mixture are of the same type. Optionally, the polymer monomers in the sulfur-containing mixture and the halogen-containing mixture are of different types.

[0066] In the embodiments of the present application, the initiator includes one or more of azobisisobutyronitrile, benzophenone, thioxanthone, camphorquinone and bisimidazole.

[0067] Optionally, the initiators in the sulfur-containing mixture and the halogen-containing mixture are of the same type. Optionally, the initiators in the sulfur-containing mixture and the halogen-containing mixture are of different types.

[0068] In the embodiment of the present application, before the subsequent steps, the two solid electrolytes (sulfide electrolyte and halide electrolyte) need to be uniformly mixed with the polymer monomer and the initiator respectively. The mixing method is one of roller milling, ball milling, high-speed mixing or three-dimensional mixing.

[0069] S102 sprays a sulfur-containing mixture on the substrate, and sprays a halogen-containing mixture on the sulfur-containing mixture to obtain an electrolyte membrane precursor.

[0070] In an embodiment of the present application, a material with release force is provided as a substrate. A sulfur-containing mixture of a preset thickness is first sprayed on the substrate to form a sulfur-containing mixture layer, and then a halogen-containing mixture of a preset thickness is continuously sprayed on the sulfur-containing mixture to form a halogen-containing mixture layer, to obtain an electrolyte membrane precursor including a substrate, a sulfur-containing mixture layer and a halogen-containing mixture layer. In subsequent steps, the sulfur-containing mixture layer will undergo a polymerization reaction to form a sulfur-containing electrolyte membrane, and the halogen-containing mixture layer will undergo a polymerization reaction to form a halogen-containing electrolyte membrane.

[0071] In the embodiments of the present application, by selecting a material with release force as the substrate, it is helpful to remove the substrate in the subsequent steps to obtain a composite solid electrolyte membrane containing a sulfide electrolyte and a halide electrolyte.

[0072] In some possible embodiments, the substrate includes one or more of a polyester film and a polytetrafluoroethylene film, wherein the advantages of the polyester film are good toughness, high tensile strength and good friction resistance, and the advantages of the polytetrafluoroethylene film are high temperature resistance, corrosion resistance, good wear resistance and good chemical resistance.

[0073] In the embodiment of the present application, the sulfur-containing mixture containing the sulfide electrolyte and the halogen-containing mixture containing the halide electrolyte are combined together by spraying, so that the sulfur-containing mixture layer and the halogen-containing mixture layer can be closely combined, which helps to reduce the interface resistance and improve the compactness of the composite solid electrolyte membrane finally formed. Moreover, the use of the spraying method facilitates the regulation of the thickness of the sulfur-containing mixture layer and the halogen-containing mixture layer, which helps to improve the ion transmission capacity of the composite solid electrolyte membrane.

[0074] In some possible embodiments, the spraying thickness of the sulfur-containing mixture is 10-300 microns. In the embodiments of the present application, the spraying thickness of the sulfur-containing mixture is preferably 30-50 microns.

[0075] Optionally, the spraying thickness of the sulfur-containing mixture is 10 microns; optionally, the spraying thickness of the sulfur-containing mixture is 155 microns; optionally, the spraying thickness of the sulfur-containing mixture is 300 microns.

[0076] In some possible embodiments, the spraying thickness of the halogen-containing mixture is 0.5-100 microns. In the embodiment of the present application, the spraying thickness of the halogen-containing mixture is preferably 5-10 microns.

[0077] Optionally, the spraying thickness of the halogen-containing mixture is 0.5 micrometers; optionally, the spraying thickness of the halogen-containing mixture is 50 micrometers; optionally, the spraying thickness of the halogen-containing mixture is 100 micrometers.

[0078] S103: The electrolyte membrane precursor is subjected to light treatment to obtain an electrolyte membrane prepolymer.

[0079] In an embodiment of the present application, the electrolyte membrane precursor obtained in step S102 is placed under an ultraviolet light source for light treatment. Under the irradiation of the ultraviolet light source, the initiator in the sulfur-containing mixture layer and the halogen-containing mixture layer will trigger a polymerization reaction between the polymer monomers, thereby connecting multiple polymer monomers uniformly dispersed in the mixture to form a polymer network. Since the sulfur-containing mixture layer and the halogen-containing mixture layer are in contact, the polymer monomers in the sulfur-containing mixture layer and the polymer monomers in the halogen-containing mixture layer will also undergo a polymerization reaction under the initiation of the initiator and connect to each other. After a period of ultraviolet light irradiation, multiple polymer monomers in the sulfur-containing mixture and the halogen-containing mixture form a polymer network that penetrates the sulfur-containing mixture layer and the halogen-containing mixture layer through a polymerization reaction, and an electrolyte membrane prepolymer can be obtained. Among them, in the electrolyte membrane prepolymer, the sulfur-containing mixture layer is converted into a prepolymerized sulfur-containing electrolyte membrane, and the halogen-containing mixture layer is converted into a prepolymerized halogen-containing electrolyte membrane.

[0080] In the embodiment of the present application, the polymer network formed by in-situ polymerization of polymer monomers under ultraviolet light supports the sulfide electrolyte and the halide electrolyte, which helps to obtain a composite solid electrolyte membrane with self-supporting ability. Compared with the existing technology for preparing composite solid electrolyte membranes, the method of adding polymer monomers for in-situ polymerization is not only conducive to mass production, but also conducive to improving the mechanical strength of the composite solid electrolyte membrane, so that the composite solid electrolyte membrane has self-supporting ability.

[0081] In the embodiment of the present application, the wavelength of the light source for the illumination treatment is 330-400 nanometers, preferably 365 nanometers.

[0082] Optionally, the wavelength of the light source for the illumination treatment is 330 nanometers; Optionally, the wavelength of the light source for the illumination treatment is 365 nanometers; Optionally, the wavelength of the light source for the illumination treatment is 400 nanometers;

[0083] In the embodiments of the present application, the time of light treatment is 1-300 seconds, preferably 10-60 seconds.

[0084] Optionally, the illumination processing time is 1 second; the illumination processing time is 150 seconds; the illumination processing time is 300 seconds.

[0085] Figure 2 is a schematic diagram of a structure of a device for spraying and light treatment provided in an embodiment of the present application, such as Figure 2 As shown, reference numeral 1 indicates a spray pot containing a sulfur-containing mixture, reference numeral 2 indicates a spray pot containing a halogen-containing mixture, reference numeral 3 indicates a nozzle of the spray pot, reference numeral 4 indicates an ultraviolet light source area, and reference numeral 5 indicates a substrate. The spraying operation in step S102 and the illumination operation in step S103 can be performed in the device.

[0086] S104 heats the electrolyte membrane prepolymer to obtain an electrolyte membrane full polymer.

[0087] In the implementation of the present application, the electrolyte membrane prepolymer obtained in step S103 is placed in an oven for heating treatment, so that the polymer monomers in the prepolymerized sulfur-containing electrolyte membrane and the prepolymerized halogen-containing electrolyte membrane can be completely polymerized to obtain an electrolyte membrane full polymer. Among them, in the electrolyte membrane full polymer, the prepolymerized sulfur-containing electrolyte membrane is converted into a fully polymerized sulfur-containing electrolyte membrane, and the prepolymerized halogen-containing electrolyte membrane is converted into a fully polymerized halogen-containing electrolyte membrane. Through heating treatment, the mechanical strength and flexibility of the sulfur-containing electrolyte membrane and the halogen-containing electrolyte membrane can be greatly increased.

[0088] In the embodiments of the present application, the temperature of the heating treatment is 30-150 degrees Celsius, preferably 40-80 degrees Celsius.

[0089] Optionally, the temperature of the heating treatment is 30 degrees Celsius; optionally, the temperature of the heating treatment is 90 degrees Celsius; optionally, the temperature of the heating treatment is 150 degrees Celsius.

[0090] In the embodiments of the present application, the heating treatment time is 0.5-48 hours, preferably 6-24 hours.

[0091] Optionally, the heating treatment time is 0.5 hours; optionally, the heating treatment time is 24 hours; optionally, the heating treatment time is 48 hours.

[0092] S105 removes the substrate in the electrolyte membrane polymer to obtain a composite solid electrolyte membrane.

[0093] In the embodiment of the present application, the substrate in the electrolyte membrane full polymer obtained in step S104 is removed to obtain a composite solid electrolyte membrane containing a sulfide electrolyte and a halide electrolyte. The composite solid electrolyte membrane is composed of a sulfur-containing electrolyte membrane and a halogen-containing electrolyte membrane. After the polymer monomers in the sulfur-containing mixture layer undergo polymerization reaction, the viscosity between the sulfur-containing electrolyte membrane converted from the sulfur-containing mixture layer and the substrate is greatly reduced, and the substrate can be easily separated from the sulfur-containing electrolyte membrane by hand or machine.

[0094] In the embodiment of the present application, the composite solid electrolyte membrane is prepared by using a method of in-situ polymerization of polymer monomers, which is beneficial to improving the mechanical strength of the composite solid electrolyte membrane and making the composite solid electrolyte membrane self-supporting. The use of spraying is beneficial to improving the compactness of the composite solid electrolyte membrane, making the sulfur-containing electrolyte membrane and the halogen-containing electrolyte membrane in the composite solid electrolyte membrane closely combined, reducing the interface resistance, and improving the ion transmission capacity of the composite solid electrolyte membrane. The preparation method is simple, efficient and convenient, and easy to realize industrialization.

[0095] In the embodiment of the present application, the composite solid electrolyte membrane comprising a sulfide electrolyte and a halide electrolyte prepared by the preparation method has the characteristics of high density, high mechanical strength, and high ionic conductivity. When the composite solid electrolyte membrane is used in an all-solid-state battery, the composite solid electrolyte membrane can provide sufficient channels for the migration of lithium ions, promote the efficient and rapid migration of lithium ions, give full play to the capacity of active substances, increase the energy density of the battery, and improve the cycle life of the battery.

[0096] The embodiment of the present application provides a composite solid electrolyte membrane. The composite solid electrolyte membrane is prepared by the above-mentioned method for preparing the composite solid electrolyte membrane. The composite solid electrolyte membrane comprises a sulfide electrolyte and a halide electrolyte, and has high mechanical strength and high ionic conductivity. It should be noted that the features and advantages described above for the method for preparing the composite solid electrolyte membrane are also applicable to the composite solid electrolyte membrane, and will not be repeated here.

[0097] The embodiment of the present application provides an all-solid-state battery. The all-solid-state battery includes the above-mentioned composite solid electrolyte membrane. When the above-mentioned composite solid electrolyte membrane is used in the all-solid-state battery, the composite solid electrolyte membrane can provide sufficient channels for the migration of lithium ions, promote the efficient and rapid migration of lithium ions, give full play to the capacity of active substances, improve the energy density of the battery, and improve the cycle life of the battery. It should be noted that the characteristics and advantages described above for the preparation method of the composite solid electrolyte membrane are also applicable to the all-solid-state battery, and will not be repeated here.

[0098] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0099] Example 1

[0100] Step 1: uniformly mix lithium phosphorus sulfur chlorine electrolyte (sulfide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) in a mass ratio of 95:5:0.05 to obtain a sulfur-containing mixture; uniformly mix lithium indium chloride solid electrolyte (halide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) in a mass ratio of 95:5:0.05 to obtain a halogen-containing mixture;

[0101] Step 2: first spray the sulfur-containing mixture obtained in step 1 on the surface of the polytetrafluoroethylene membrane (spraying thickness 50 microns), and then spray the halogen-containing mixture obtained in step 1 on the surface of the sulfur-containing mixture (spraying thickness 5 microns) to obtain an electrolyte membrane precursor;

[0102] Step 3: prepolymerizing the electrolyte membrane precursor obtained in step 2 by using an ultraviolet light source, the illumination time is 20 seconds, and obtaining an electrolyte membrane prepolymer;

[0103] Step 4: heating the electrolyte membrane prepolymer obtained in step 3 at a temperature of 60 degrees Celsius for 12 hours to obtain an electrolyte membrane full polymer;

[0104] Step 5: Remove the substrate in the electrolyte membrane polymer obtained in step 4 to obtain a composite solid electrolyte membrane.

[0105] Example 2

[0106] The spraying thickness of the sulfur-containing mixture sprayed on the surface of the polytetrafluoroethylene membrane in step 2 of Example 1 was changed to 80 μm, and the other conditions were the same as those in Example 1 to obtain a composite solid electrolyte membrane.

[0107] Example 3

[0108] The spraying thickness of the halogen-containing mixture sprayed on the surface of the sulfur-containing mixture in step 2 of Example 1 was changed to 10 μm, and the other conditions were the same as those in Example 1 to obtain a composite solid electrolyte membrane.

[0109] Example 4

[0110] The illumination time in step 3 of Example 1 was changed to 10 seconds, and the other conditions were the same as those of Example 1 to obtain a composite solid electrolyte membrane.

[0111] Example 5

[0112] The heating temperature in step 4 of Example 1 was changed to 50 degrees Celsius, and the other conditions were the same as those of Example 1 to obtain a composite solid electrolyte membrane.

[0113] Example 6

[0114] The heating time in step 4 of Example 1 was changed to 20 hours, and the other conditions were the same as those of Example 1 to obtain a composite solid electrolyte membrane.

[0115] Comparative Example 1

[0116] Step 1: uniformly mix lithium phosphorus sulfur chlorine electrolyte (sulfide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) in a mass ratio of 95:5:0.05 to obtain a sulfur-containing mixture; uniformly mix lithium indium chloride solid electrolyte (halide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) in a mass ratio of 95:5:0.05 to obtain a halogen-containing mixture;

[0117] Step 2: spraying the sulfur-containing mixture obtained in step 1 on the surface of the polytetrafluoroethylene membrane (spraying thickness 50 microns); using an ultraviolet light source to prepolymerize the sulfur-containing mixture sprayed on the surface of the polytetrafluoroethylene membrane, the illumination time is 20 seconds; heating the sulfur-containing mixture sprayed on the surface of the polytetrafluoroethylene membrane, the heating temperature is 60 degrees Celsius, the heating time is 12 hours, so that the sulfur-containing mixture is converted into a sulfur-containing electrolyte membrane, and a sulfur-containing electrolyte membrane full polymer is obtained;

[0118] Step 3: spraying a halogen-containing mixture on the surface of the sulfide electrolyte membrane in the sulfur-containing electrolyte membrane full polymer obtained in step 2 (spraying thickness is 5 μm); using an ultraviolet light source to prepolymerize the halogen-containing mixture sprayed on the surface of the sulfide electrolyte membrane, the illumination time is 20 seconds; heating the halogen-containing mixture sprayed on the surface of the sulfide electrolyte membrane, the heating temperature is 60 degrees Celsius, the heating time is 12 hours, so that the halogen-containing mixture is converted into a halogen-containing electrolyte membrane, and a halogen-containing electrolyte membrane full polymer is obtained;

[0119] Step 4: remove the substrate in the electrolyte membrane polymer obtained in step 3 to obtain a composite solid electrolyte membrane.

[0120] Comparative Example 2

[0121] The mass ratio of lithium phosphorus sulfur chlorine electrolyte (sulfide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) in step 1 of Example 1 is changed to 70:30:0.3, and the mass ratio of lithium indium chloride electrolyte (halide electrolyte), methyl methacrylate monomer (polymer monomer), and azobisisobutyronitrile (initiator) is changed to 70:30:0.3. The other conditions are the same as those in Example 1 to obtain a composite solid electrolyte membrane.

[0122] The density and ion conductivity of the composite solid electrolyte membrane obtained in Examples 1-6 and Comparative Examples 1-2 were tested. The composite solid electrolyte membrane obtained in Examples 1-6 and Comparative Examples 1-2 was applied to an all-solid-state battery, and ternary nickel cobalt lithium manganese oxide was selected as the positive electrode active material and metallic lithium was selected as the negative electrode to assemble the principle half-cell, and the first discharge specific capacity at the positive electrode rate of 0.1C was tested. The test results are shown in Table 1.

[0123] Table 1

[0124]

[0125]

[0126] From the data results of Examples 1, 2 and 3, it can be seen that when the spraying thickness of the sulfur-containing mixture and the halogen-containing mixture increases, the path of ion shuttle electrolyte membrane layer in the all-solid-state battery becomes longer, thereby affecting the specific capacity of the positive electrode material.

[0127] From the data results of Example 1, Example 4, Example 5, and Example 6, it can be seen that the illumination time, heating temperature, and heating time all affect the degree of polymerization of the polymer monomer. When the illumination time is shortened or the heating temperature is lowered, the density of the composite solid electrolyte membrane decreases; when the heating time is increased, the density of the composite solid electrolyte membrane increases. The increase in the density of the composite solid electrolyte membrane is conducive to ion transmission, thereby improving the specific capacity of the positive electrode material in the battery.

[0128] From the data results of Example 1 and Comparative Example 1, it can be seen that: when the sulfur-containing mixture layer is first polymerized to form a sulfur-containing electrolyte membrane, the surface morphology is relatively dense; when a halogen-containing electrolyte membrane is prepared on the sulfur-containing electrolyte membrane, the bonding between the two layers of the electrolyte membrane is not tight enough, which increases the interface resistance and is not conducive to the specific capacity of the positive electrode material in the battery.

[0129] From the data results of Example 1 and Comparative Example 2, it can be seen that: when the proportion of polymer monomers in the sulfur-containing mixture and the halogen-containing mixture is too high, the polymer network formed after the polymer monomers are completely polymerized hinders the contact between the solid electrolyte particles, reduces the ionic conductivity of the composite solid electrolyte membrane, and is not conducive to the specific capacity of the positive electrode material in the battery.

[0130] It should be noted that the above-mentioned sequence of the embodiments of the present application is for description only and does not represent the advantages and disadvantages of the embodiments. The above-mentioned specific embodiments of this specification are described. Other embodiments are within the scope of the attached claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0131] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the device embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.

[0132] A person skilled in the art will understand that all or part of the steps to implement the above embodiments may be accomplished by hardware or by instructing related hardware through a program, and the program may be stored in a computer-readable storage medium, and the above-mentioned storage medium may be a read-only memory, a disk or an optical disk, etc.

[0133] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: include: The sulfide electrolyte and the halide electrolyte are respectively mixed with the polymer monomer and the initiator to obtain a sulfur-containing mixture and a halogen-containing mixture; Spraying the sulfur-containing mixture on a substrate, and spraying the halogen-containing mixture on the sulfur-containing mixture to obtain an electrolyte membrane precursor; The electrolyte membrane precursor is subjected to light treatment to obtain an electrolyte membrane prepolymer; The electrolyte membrane prepolymer is subjected to a heating treatment to obtain an electrolyte membrane full polymer; The substrate in the electrolyte membrane polymer is removed to obtain a composite solid electrolyte membrane.

2. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the sulfur-containing mixture, the mass proportions of the sulfide electrolyte, the polymer monomer and the initiator are 80%-99%, 1%-20% and 0.01%-1% respectively; In the halogen-containing mixture, the mass proportions of the halide electrolyte, the polymer monomer and the initiator are 80%-99%, 1%-20% and 0.01%-1% respectively.

3. The method for preparing a composite solid electrolyte membrane according to claim 2, characterized in that: The sulfide electrolyte includes one or more of a lithium germanium phosphorus sulfur electrolyte and a lithium phosphorus sulfur chlorine electrolyte; The halide electrolyte includes one or more of a lithium yttrium bromine electrolyte, a lithium indium chlorine electrolyte, a lithium indium bromine electrolyte and a lithium zirconium chlorine electrolyte; The polymer monomers include one or more of butyl acrylate, polyethylene glycol diacrylate, methyl methacrylate, trifluoroethyl methacrylate and pentaerythritol triacrylate; The initiator includes one or more of azobisisobutyronitrile, benzophenone, thioxanthone, camphor porquinone and bisimidazole.

4. The method for preparing a composite solid electrolyte membrane according to claim 3, characterized in that: The median particle size of the sulfide electrolyte is 0.3-10 microns. The median particle size of the halide electrolyte is 0.3-10 microns.

5. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The mixing method is one of roller milling, ball milling, high-speed mixing or three-dimensional mixing.

6. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The substrate comprises one or more of a polyester film and a polytetrafluoroethylene film; The spraying thickness of the sulfur-containing mixture is 10-300 microns; The spraying thickness of the halogen-containing mixture is 0.5-100 microns.

7. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The wavelength of the light source for the light treatment is 330-400 nanometers; The light treatment time is 1-300 seconds.

8. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: The temperature of the heating treatment is 30-150 degrees Celsius; The heating treatment time is 0.5-48 hours.

9. A composite solid electrolyte membrane, characterized in that: The composite solid electrolyte membrane is prepared by the method for preparing a composite solid electrolyte membrane according to any one of claims 1 to 8.

10. An all-solid-state battery, characterized in that: Comprising the composite solid electrolyte membrane as claimed in claim 9.

Citation Information

Cited By

  • Composite solid electrolyte, preparation method thereof and secondary battery containing composite solid electrolyte

    CN122091709A

  • Composite solid electrolyte, method for preparing the same, and secondary battery including the same

    CN122091709B